Type III Secretion in the Melioidosis Pathogen Burkholderia pseudomallei - Vander Broek, Charles W.; Stevens, Joanne M. (Frontiers in Cellular and Infection Microbiology, 2017)
Burkholderia pseudomallei is a Gram-negative intracellular pathogen and the causative agent of melioidosis, a severe disease of both humans and animals. Melioidosis is an emerging disease which is predicted to be vastly under-reported. Type III Secretion Systems (T3SSs) are critical virulence factors in Gram negative pathogens of plants and animals. The genome of B. pseudomallei encodes three T3SSs. T3SS-1 and -2, of which little is known, are homologous to Hrp2 secretion systems of the plant pathogens Ralstonia and Xanthomonas. T3SS-3 is better characterized and is homologous to the Inv/Mxi-Spa secretion systems of Salmonella spp. and Shigella flexneri, respectively. Upon entry into the host cell, B. pseudomallei requires T3SS-3 for efficient escape from the endosome. T3SS-3 is also required for full virulence in both hamster and murine models of infection. The regulatory cascade which controls T3SS-3 expression and the secretome of T3SS-3 have been described, as well as the effect of mutations of some of the structural proteins. Yet only a few effector proteins have been functionally characterized to date and very little work has been carried out to understand the hierarchy of assembly, secretion and temporal regulation of T3SS-3. This review aims to frame current knowledge of B. pseudomallei T3SSs in the context of other well characterized model T3SSs, particularly those of Salmonella and Shigella.